PENGARUH EKSPEKTASI KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PRODUK LUXCRIME BLUR & COVER TWO WAY CAKE DI SHOPEE - Lusia Wibowo, Marvela; Setyabudi, Djoko; Manalu, S. Rouli (Interaksi Online, 2024)
The trend of using beauty products is increasing rapidly due to the emergence of awareness from the public to take care of beauty. This is also supported by the spread of e-commerce that carries the marketplace concept, including Shopee, Tokopedia, BliBli, and so on. One of the local cosmetic brands that uses e-commerce as its trading activity is Luxcrime. One of the Luxcrime sales categories that are in great demand by the public is Blur & Cover Two Way Cake. The problem that occurs is the number of complaints that arise from consumers regarding the quality of products and services on the Luxcrime Mall platform at Shopee. This study aims to determine the effect of product quality expectations and service quality on customer satisfaction with Luxcrime Blur & Cover Two Way Cake products. This study uses the explanaotri method with non probability sampling technique involving 100 respondents. The theory used is Expectancy Disconfirmation Theory as a foundation for understanding the effect of product quality expectations and service quality on customer satisfaction on Luxcrime Blur & Cover Two Way Cake products. The results of the research obtained through multiple linear regression hypothesis testing are that product quality expectations and service quality expectations have a simultaneous influence on customer satisfaction with a significance value obtained of 0.000. This means that every time there is an increase in the value of X1 and X2, there is also an increase in the value of Y so that the hypothesis can be accepted.